Data aggregation and pipelining scheduling protocols for real–time wireless sensor networks. (15th January 2013) - Ouni, Sofiane; Gherairi, Salsabil; Kamoun, Farouk
Critical applications in real–time wireless sensor networks require bounded service latency and energy consumption optimisation. This motivates us to design a novel scheduling approach, which integrates communications with pipelining and data aggregation. The aim of our aggregation technique is to reduce the number of messages, which consequently reduces energy consumption. However, our pipelining technique is defined to minimise communication latency. Our approach is applied on tree wireless sensor networks and in a real–time context, which requires communications without interference. Thus, we use TDMA and a multi–frequency access method based on parent relationship clustering. In this context, we made the necessary mathematical formulation to determine communication response time and to predict the impact of real–time constraints, particularly deadlines, on communication delay. Our simulations outperform the efficiency of our approach to comprise between communication delay and energy consumption constraints.